Information Radiology Diagnostics in Traumatology (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The rapid development of diagnostic radiology observed in the last two decades has opened up fundamentally new opportunities for clinical medicine, making almost all organs and tissue structures of the human body available for research. To develop and improve new methods of radiation diagnostics in traumatology and orthopedics, 145 patients with various injuries and diseases of the musculoskeletal system were examined using radiography, ultrasound, CT, and MRI. Largely due to the success of radiation diagnostics in the leading clinics of the world, the time from the patient’s admission to the hospital to the diagnosis does not exceed 40-60 minutes. Radiation research methods have long been in second place in terms of the frequency of their use, second only to the most common and mandatory laboratory tests. Data from statistical studies of major global medical centers show that it is thanks to radiation methods that the number of erroneous diagnoses during a patient’s initial visit today does not exceed 4% [1-3]. Classical radiology in many areas of surgery, therapy, and cardiology no longer plays a leading role in the production of medical images. According to WHO, about 80% of diagnoses are made through the direct use of radiation research materials. In this regard, modern radiation diagnostics, which has various methods of visual control, is increasingly focused on comprehensive solutions to diagnostic and therapeutic problems using new methods. 100% of orthopedic and traumatology patients require examinations using radiological diagnostic methods. 85% of the information necessary for making a decision on treatment is provided by radiation diagnostic methods (in traumatology and orthopedics - up to 100%).